Effectiveness of GeoGebra-aided problem-solving in teaching geometry at the senior secondary school level - Reginald-Ihedike, Melody; Ojimba, Daso Peter (Faculty of Natural and Applied Sciences Journal of Mathematics, and Science Education, 2022)
This study investigated the instructional effectiveness of Dynamic Geometry Software in teaching geometry in senior secondary schools in Obio/Akpor Local Government Area of Rivers State, Nigeria. The pre-test-post-test non-equivalent intact class quasi-experimental research design was used. A sample of 115 Senior Secondary Class II (SSC2) students took part in the study. There were 61 students in the experimental group and 54 students in the benchmark group. The Geometry Problem-solving Achievement Test (GPAT) was used for data collection. The GPAT was a 25-item multiple-choice questions and it was used to measure the achievement of the students in Geometry. The instrument was validated by experts in Mathematics Education. The reliability coefficient of GPAT was 0.82 using the test-retest method. The findings among others have it that GeoGebra-supplemented problem-solving instructions significantly advanced the achievement of students in Geometry. However, the male students slightly outperformed their female counterparts taught with GeoGebra and the students aged 16 and above had higher achievement scores than their counterparts aged 10–15 years. It was recommended, among others, that the use of GeoGebra in the teaching and learning process conforms to 21st-century education where the teacher is seen as a facilitator of learning, not all-knowing.